2002
DOI: 10.1002/mas.10016
|View full text |Cite
|
Sign up to set email alerts
|

Peptide mapping of proteins in human body fluids using electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Human body fluids have been rediscovered in the post-genomic era as great sources of biological markers and perhaps particularly as sources of potential protein biomarkers of disease. Analytical tools that allow rapid screening, low sample consumption, and accurate protein identification are of great importance in studies of complex biological samples and clinical diagnosis. Mass spectrometry is today one of the most important analytical tools with applications in a wide variety of fields. One of the fastest g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 51 publications
0
113
0
Order By: Relevance
“…Aliquots of 5 μL of plasma from 1,060 individuals, diluted to 20 μL in 50 mM ammonium bicarbonate (NH4HCO3) were centrifuged 16,000 × g for 10 min in 5°C. From the supernatant, 16 μL was digested following the previously published protocol (28). Briefly the plasma samples were transferred into a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of 5 μL of plasma from 1,060 individuals, diluted to 20 μL in 50 mM ammonium bicarbonate (NH4HCO3) were centrifuged 16,000 × g for 10 min in 5°C. From the supernatant, 16 μL was digested following the previously published protocol (28). Briefly the plasma samples were transferred into a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the potential of FT-ICR MS for complex mixture elucidation, e.g., crude oil samples [28], peptide mixtures from digestion procedures [29], or glycoconjugate mixtures [30]. McClellan et al have studied the fragmentation of regularly sulfated CS-oligosaccharides by use of SORI-CID FT-ICR MS [16] and Aguilan et al demonstrated the potential of Nano-ESI FT-ICR MS for the analysis of ␣-carrageenan sulfated oligosaccharides [31].…”
mentioning
confidence: 99%
“…6 A detailed description of the sample preparation including information on employed protocols for LC and CE is available in the original research articles and reviews. 47,48 …”
Section: Samples and Sample Preparationmentioning
confidence: 99%